Islamic Education as a Science: An Ontological, Epistemological, and Axiological Review - Mukhtar Mas’ud (Program Pascasarjana UIN Sumatera Utara, 2024)
This study aims to examine the standing of Islamic education as a scientific discipline through ontological, epistemological, and axiological reviews, correlating these with the characteristics of Islamic teachings in religion, worship, creed, science, and culture. This research employs a qualitative library research method with a philosophical and descriptive-analytical approach. Primary data sources include the Qur'an, Hadith, and classical works of Muslim philosophers such as Al-Ghazali and Ibn Sina, while secondary sources consist of contemporary books and journals. Data collection uses documentation techniques, and data analysis is conducted using content analysis and logical synthesis. The findings reveal that ontologically, Islamic education encompasses a holistic view of reality, including both material and non-material aspects. Epistemologically, it constructs knowledge through the integration of naqli (revealed) and aqli (rational) arguments via analytical and synthetical methods. Axiologically, Islamic education contains both physical and spiritual values, with religious value as the highest objective. In conclusion, Islamic education fully meets the criteria as a valid and universal scientific discipline, holding significant relevance in addressing modern challenges. Strengthening this philosophical foundation is essential for formulating contextual and civilization-oriented Islamic education policies